POLÍTICAS PÚBLICAS PARA A EDUCAÇÃO INFANTIL NO BRASIL: dimensões da oferta, acesso e qualidade - Petula Ramanauskas Santorum e Silva (Universidade Federal do Maranhão, 2019)
Public policies for early childhood education in Brazil, considering the dimensions of supply, access and quality, are lacking in terms of guaranteeing the right of young children to education. Through exploratory research, the purpose of this study was to discuss such “gaps” through their identification and discussion. The study reveals that access to the vacancy and the permanence of the child in this stage of education poses as one of the challenges the reduction of the disparities in access, especially for socioeconomic reasons. It is known that children with families with less or no purchasing power have been left out of this right. The study revealed that the municipalities need to expand the offer of care, without marginalizing the quality of services offered, not only providing access, but also ensuring full-time permanence.